The weirdness of being : Heidegger's unheard answer to the Seinsfrage - De Gennaro, Ivo; Cambridge eBooks (Durham : Acumen Publishing, 2013)
The ongoing publication of Heidegger's complete works has called into question the interpretive and translative practices that have historicized Heidegger's thinking through the adaptation of categories and mind-sets inherited from metaphysics. Ivo De Gennaro argues that the posthumous treatises in particular - many of which have yet to be translated into English - show that the 'other onset of thinking' that Being and Time inaugurated and which those historicizing accounts have interpreted and translated away, has already taken place. This book, on the other hand, speaks solely from that other onset, that of being itself. While arguing the 'one-pointedness' of Heidegger's entire path of thinking, De Gennaro draws mainly on the posthumous treatises to offer both a provisional exploration of, and an introduction to, a thinking whose sense and implications have barely begun to emerge. This challenging and original interpretation marks an important contribution to Heidegger scholarship.
Machine generated contents note: 1. Why being itself and not just being? -- 1.1. Seinsfrage and Denkweg -- 1.2. Three meanings of the word Sein -- 1.3. The ground-theme of Being and Time -- 1.4. What does Moglichkeit mean? -- 1.5. Translating Moglichkeit -- 1.6. The word of the Seinsfrage -- 2. Owning to the belongingness to being -- 2.1. Enowned owning and the stress for words -- 2.2. Translating Seyn -- 2.3. Translating Geschichte -- 2.4. Returnership -- 3. Translation, tradition, and the other onset of thinking -- 3.1. Onset and Unterschied -- 3.2. Tradition as translation -- 3.3. The Denkweg-sense of interpretation -- 4. Husserl and Heidegger on Dasein -- 4.1. The word Dasein -- 4.2. Husserl on Dasein and the scope of transcendental phenomenology -- 4.3. Heidegger on Da-sein and the scope of the Seinsfrage -- 4.4. Coining Da-sein in English -- 5. Minding that "we" cannot ever not think be3ng -- 5.1. Who is "we"? -- 5.2. Enowning as the word -- 5.3. The word-treasure of enowning -- 5.4. Translating Wesen -- 5.5. Translating Da-seyn -- 5.6. Minding the mind -- 6. The origin of speech -- 6.1. Da-sein and the de-homination of man -- 6.2. The temper of silence.
Title from publisher's bibliographic system (viewed on 02 Oct 2015).
Keywords: Heidegger, Martin, -- 1889-1976.; Heidegger, Martin, -- 1889-1976.; Ontology; Philosophy -- Translations -- History and criticism; Electronic books